Control of soybean rust by fungicides - K.H. ANAHOSUR, P.V. PATIL and (Indian Phytopathology, 2002)
Field trials were conducted at 2 locations, the Main Research Station, Dharwad and the Research & Development Unit, Ugarkhurd, Karnataka, India, during kharif 1995 to test the efficacy of 7 fungicides (mancozeb, tridemorph, triadimefon, difenoconazole, chlorothalonil, propiconazole and hexaconazole) against soyabean rust caused by Phakospora pachyrhizi. Hexaconazole, triadimefon and propiconazole @ 0.1% sprayed at 15 day intervals starting from the onset of disease were effective in reducing the percentage disease index (PDI) by 25.2%, 32.8% and 32.8%, respectively, with significant increases in seed yield and 100 seed weight. The highest benefit:cost ratio (9.3) was recorded with hexaconazole followed by propiconazole (4.0) and triadimefon (1.9).Oil and protein content in hexaconazole (16.8% and 38.4%), propiconazole (16.8% and 38.6%) and triadimefon (16.7% and 38.6%) sprayed plots were also the highest recorded.